DEVELOPMENT STRATEGY ON ANGING MAMMIRI BEACH, MAKASSAR CITY, INDONESIA - Katarina Avrillia Putri Batha Nida (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
This study aims to formulate an effective strategy for the development of Anging Mammiri Beach in Makassar City, focusing on harnessing the potential of natural resources and enhancing the role of local communities and related stakeholders. The method employed is qualitative research, with data collection conducted through in-depth interviews with local communities, business actors, and the local government, which took place in 2025. The results of the study identified that Anging Mammiri Beach still lacks cooperation between stakeholders, including the government, local communities, academics, and the still minimal role of local communities living around the beach. This study found that the local community is the primary manager of Anging Mammiri Beach; however, there is still very little involvement and a lack of concern for its potential. Recommended strategies include increased collaboration between stakeholders, the development of environmentally friendly infrastructure, social media-based digital marketing to attract tourists, and strengthening the empowerment of local human resources in tourism management. The development of Anging Mamiri Beach must prioritize an integrated approach that combines economic, social, and environmental aspects in a sustainable manner. The recommendations in this strategy can enhance tourist appeal, increase the number of visits, provide economic benefits for the surrounding community, and help preserve the coastal environment for the benefit of future generations. The role of the government is also needed to carry out operational and collaborative efforts to optimize the management and development of Anging Mamiri Beach. Furthermore, there is a need for consensus among the local community, government, academics, and stakeholders to develop an appropriate strategy for this beach. With good collaboration between stakeholders, the development strategy for Anging Mamiri Beach can be precisely targeted, increasing the number of tourist visits and enabling it to compete with other beaches.